Virome analysis of an ectomycorrhizal fungus Suillus luteus revealing potential evolutionary implications - Liu, Hanzhao; Zhang, Yifei; Liu, Yingying; Xiao, Junbo; Huang, Zijie; Li, Yunfeng; Li, Huaping; Li, Pengfei (Frontiers in Cellular and Infection Microbiology, 2023)
Suillus luteus is a widespread edible ectomycorrhizal fungus that holds significant importance in both ecological and economic value. Mycoviruses are ubiquitous infectious agents hosted in different fungi, with some known to exert beneficial or detrimental effects on their hosts. However, mycoviruses hosted in ectomycorrhizal fungi remain poorly studied. To address this gap in knowledge, we employed next-generation sequencing (NGS) to investigate the virome of S. luteus. Using BLASTp analysis and phylogenetic tree construction, we identified 33 mycovirus species, with over half of them belonging to the phylum Lenarviricota, and 29 of these viruses were novel. These mycoviruses were further grouped into 11 lineages, with the discovery of a new negative-sense single-stranded RNA viral family in the order Bunyavirales. In addition, our findings suggest the occurrence of cross-species transmission (CST) between the fungus and ticks, shedding light on potential evolutionary events that have shaped the viral community in different hosts. This study is not only the first study to characterize mycoviruses in S. luteus but highlights the enormous diversity of mycoviruses and their implications for virus evolution.